Method for removal of iodine oxyanions from liquids using zirconium-based metal-organic frameworks and their regeneration
Zirconium-based MOF-808 effectively addresses the challenges of removing iodine species from water by offering high iodate capture capacity and regeneration capabilities, achieving ultra-low concentrations not attainable with traditional methods.
Patent Information
- Application Number
- JP2024556262
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-24
- Filing Date
- 2023-03-23
- Publication Date
- 2025-04-14
AI Technical Summary
Current methods for removing iodine species, particularly iodate, from water are limited by slow speeds, low uptake volumes, and the phenomenon of 'sloughage,' which makes it difficult to achieve ultra-low concentrations below 10 ppb using traditional ion exchange resins.
The use of zirconium-based metal organic frameworks (MOFs), such as MOF-808, for the adsorption of iodine species from liquid streams, combined with a regeneration process using acid washes to maintain high adsorption performance.
MOF-808 demonstrates a high capacity for iodate capture, achieving up to 233 mg/g, and effectively reduces wastewater concentrations of iodine species to ultra-low levels, overcoming the limitations of traditional methods.
Smart Images

Figure 2025510039000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention, including its various embodiments, relates to the removal of selected chemical species from liquids. In particular, the present invention and its embodiments relate to the use of metal-organic frameworks (MOFs), such as MOF-808, which have particular properties that make them suitable for removing iodine species, such as oxyanions of iodine, including iodates, from liquids or liquid streams. [Background technology]
[0002] For example, if the nuclear fuel cladding were to be breached while the fuel was in use or while spent nuclear fuel was being stored during operation of a nuclear power plant, 129 I and 131 Radioactive isotopes of iodine, such as I, are produced as fission products during nuclear power generation and can enter water-based coolants and ultimately the environment. 129 I is of particular concern because it has an extremely long half-life of 15.7 million years. Radioactive isotopes of iodine form iodide (I - ) and its oxyanion, iodate (IO 3- Both species are readily soluble in water and can easily enter the human body through ingestion of contaminated water or crops, and through inhalation. Exposure to radioactive isotopes of iodine can cause problems with hormone production and thyroid diseases, including cancer.
[0003] Many studies on removing iodine species from water have been conducted using I - The focus is on removing IO. 3- Current materials for removal are often limited by slow kinetics or low uptake capacity, requiring large amounts of adsorbent for sufficient uptake. Furthermore, research into the use of metal-organic frameworks (MOFs) as adsorption platforms for iodine is still limited, with only a small proportion of gaseous I 2 The focus has been on the adsorption of
[0004] Even in the absence of competing anionic impurities in the water stream, the ability of typical ion exchange resins to reduce wastewater concentrations of iodate, for example to desirable ultra-low levels, is thermodynamically limited by the kinetic re-release of captured iodine anions unless purified wastewater is returned. Such a phenomenon is called "equilibrium sloughage." Such sloughage makes the use of typical resin-based separation media virtually impossible to remove, for example, iodates in aqueous wastewater to levels below about 10 ppb.
[0005] Thus, new technologies are needed to effectively and efficiently remove these iodine species from water and other liquid streams, such as those used or produced in the production of nuclear power or other industrial water-based streams, or from stored volumes of liquid. Technologies are needed that will remove these impurities in the presence of other competing species, or species that may compete for removal, thereby effectively reducing the removal efficiency of the species being removed. Technologies are also needed that will specifically target the capture of the impurities and remove them in a manner that minimizes reversibility or release from capture, thereby retaining the impurities at a much higher binding energy. In particular, a different type of structured media is needed to specifically address the removal of low levels of certain species, such as iodine species, that have a binding energy high enough to maintain nearly irreversible uptake as the concentration of the analyte decreases and the concentration of the competing species increases at the same time. Summary of the Invention [Means for solving the problem]
[0006] In general, the present invention relates to a method for removing iodine species from a liquid or liquid stream. In particular, the present invention relates to the use of metal-organic frameworks (MOFs), such as zirconium-based MOFs, such as MOF-808, to adsorb iodine species from a liquid or liquid stream. MOF-808 has a very high iodate uptake capacity and the Zr of the MOF 6It has been found to be of the order of 233 mg / g, corresponding to 1.63 iodate anions per metal node.
[0007] In some embodiments, the iodine species in the liquid or liquid stream is 129 I and 131 The radioisotope may be a radioisotope of iodine, such as I, which is dissolved in a liquid or liquid stream as iodide, I - , or iodate, IO 3- In some embodiments, MOF-808 may exist as an oxyanion of iodine, such as iodate, IO 3- and in some embodiments, the ammonium form of MOF-808 adsorbs iodine oxyanions such as iodide, I - In some embodiments, the liquid or liquid stream containing iodine species may include a coolant stream or other liquid stream in a nuclear power plant, or a liquid in contact with spent nuclear fuel.
[0008] The present invention also relates to methods of regenerating adsorbents such as MOFs, including zirconium-based MOFs such as MOF-808. In some embodiments, regenerating the MOFs includes using an acid wash to remove adsorbed iodine species. In some embodiments, the acid wash can be an aqueous solution of hydrochloric acid, including solutions having up to about 10% hydrochloric acid. In some embodiments, up to three washes are used, such that the regenerated MOFs have little or no effect on subsequent adsorption performance.
[0009] The present invention provides the ability to remove a variety of iodine species from liquids or liquid streams using MOFs. The present invention offers significant advantages over other technologies for removing iodine species, particularly iodates, from liquids or liquid streams, particularly those associated with nuclear power plants. [Brief description of the drawings]
[0010] [Figure 1] 1A-1C illustrate a zirconium-based MOF, namely MOF-808, according to one embodiment of the present invention.
[0011] [Figure 2A] FIG. 2A illustrates the powder X-ray diffraction pattern of as-synthesized MOF-808 compared to a simulated pattern according to one embodiment of the present invention.
[0012] [Figure 2B] FIG. 2B illustrates 1H NMR spectroscopy of MOF-808 showing the loss of formate protons, according to one embodiment of the present invention.
[0013] [Figure 2C] FIG. 2C illustrates the nitrogen adsorption-desorption isotherm and pore size distribution of the as-synthesized MOF-808 according to one embodiment of the present invention.
[0014] [Figure 2D] FIG. 2D shows a scanning electron microscope (SEM) image of as-synthesized MOF-808 crystallites, according to one embodiment of the present invention.
[0015] [Diagram 3] FIG. 3A illustrates the kinetics of iodate adsorption using MOF-808 according to one embodiment of the present invention.
[0016] FIG. 3B illustrates a Langmuir plot of the adsorption of iodate on MOF-808 according to one embodiment of the present invention.
[0017] [Figure 4A-B] FIG. 4A illustrates a density functional theory (DFT) optimized model of a MOF-808 node with bridging iodate ions, according to one embodiment of the present invention.
[0018] FIG. 4B illustrates the simulated differential pair distribution function (dPDF) of the DFT model of FIG. 4A according to one embodiment of the present invention, experimental dPDF data for MOF-808 loaded with iodate, and a simulated dPDF with unbound iodate.
[0019] [Figure 4C] FIG. 4C illustrates diffuse reflectance infrared Fourier transform spectroscopy data of untreated and iodate-loaded MOF-808, according to one embodiment of the present invention.
[0020] [Diagram 5] FIG. 5A illustrates a DFT optimized model of a MOF-808 node with bridging iodate ions, according to one embodiment of the present invention.
[0021] FIG. 5B illustrates a simulated dPDF of the DFT model of FIG. 5A, experimental dPDF data for MOF-808 loaded with iodate, and a simulated dPDF with unbound iodate, according to one embodiment of the present invention.
[0022] [Figure 6] FIG. 6A illustrates a DFT optimized model of a MOF-808 node with bridging iodate ions according to another embodiment of the present invention.
[0023] FIG. 6B illustrates a simulated dPDF of the DFT model of FIG. 6A, experimental dPDF data of MOF-808 loaded with iodate, and a simulated dPDF with unbound iodate, according to another embodiment of the present invention.
[0024] [Figure 7] FIG. 7A illustrates a DFT optimized model of a MOF-808 node with bridging iodate ions according to another embodiment of the present invention.
[0025] FIG. 7B illustrates a simulated dPDF of the DFT model of FIG. 7A, experimental dPDF data for MOF-808 loaded with iodate, and a simulated dPDF with unbound iodate, according to another embodiment of the present invention.
[0026] [Figure 8] FIG. 8A illustrates a DFT optimized model of a MOF-808 node with bridging iodate ions according to another embodiment of the present invention.
[0027] FIG. 8B illustrates a simulated dPDF of the DFT model of FIG. 8A, experimental dPDF data for MOF-808 loaded with iodate, and a simulated dPDF with unbound iodate, according to another embodiment of the present invention.
[0028] [Figure 9] FIG. 9A illustrates a powder X-ray diffraction pattern of MOF-808 according to one embodiment of the present invention.
[0029] FIG. 9B illustrates the isotherms of various morphologies of MOF-808 according to one embodiment of the present invention.
[0030] [Figure 10] 10A-10D show SEM images and SEM-EDS line scan analysis of iodine, zirconium, and MOF-808 crystallites according to one embodiment of the present invention.
[0031] [Figure 11] 11A-11D illustrate the adsorption and desorption cycle of iodate in MOF-808 according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] The present invention will be described in more detail below with reference to the accompanying drawings. The present invention will be described in conjunction with various embodiments, which should be viewed as examples and not as limiting the embodiments of the present invention or showing the only embodiment. Rather, the present invention includes various embodiments or forms, various related aspects or features, and various applications, as well as the above-mentioned alternatives, modifications, and equivalents, all of which are within the spirit and scope of the present invention and the claims, whether or not expressly described herein. Furthermore, the terms "invention", "the present invention", "embodiment", and the like, used throughout this description are used broadly and are not intended to imply that the invention requires or is limited to the specific embodiment or aspect described, or that such description is the only way the invention can be made or used.
[0033] In general, the present invention relates to a method for removing iodine species from a liquid or liquid stream. In particular, the present invention relates to the use of metal-organic frameworks (MOFs), such as zirconium-based MOFs, such as MOF-808, to adsorb iodine species from a liquid or liquid stream. MOF-808 has a very high uptake capacity for iodate, on the order of 233 mg / g of Zr of the MOF. 6 It has been found that each metal node corresponds to 1.63 iodate anions.
[0034] In some embodiments, the iodine species in the liquid or liquid stream is 129 I and 131 I is a radioactive isotope of iodine, such as I, which in liquids or liquid streams is called iodide, I - , or iodate, IO 3- In some embodiments, MOF-808 can exist as an oxyanion of iodine, such as iodate, IO 3- In some embodiments, the ammonium form of MOF-808 adsorbs iodide, I -In some embodiments, the liquid or liquid stream containing iodine species may include a coolant stream or other liquid stream in a nuclear power plant, or a liquid in contact with spent nuclear fuel.
[0035] The present invention also relates to methods of regenerating adsorbents such as MOFs, including zirconium-based MOFs such as MOF-808. In some embodiments, regenerating the MOFs includes using an acid wash to remove adsorbed iodine species. In some embodiments, the acid wash may be an aqueous solution of hydrochloric acid, including solutions having up to about 10% hydrochloric acid. In some embodiments, up to three washes may be used, such that the regenerated MOF has little or no effect on subsequent adsorption performance.
[0036] Various specific aspects of the invention are described below, including the structure of the MOFs used in the invention, their synthesis and adsorption capacity. In addition, methods of using the MOFs of the invention to remove various iodine species are described, followed by methods of regenerating the MOFs of the invention. In addition, other variations of these embodiments are also described.
[0037] Metal-organic frameworks (MOFs) are coordination polymers consisting of metal centers connected to each other by molecular organic ligands forming a network, which often self-assemble to form crystalline and highly porous materials. The metal nodes can be single metal ions, chains, or clusters, and the organic ligands, i.e., linkers, can be di-, tri-, or tetratopic. Due to the vast number of combinations of metals and organic linkers and the large number of accessible topologies, MOFs can be designed to have large surface areas, persistent porosity, and high thermal and chemical stability. In particular, the use of Zr as a metal node has been shown to be a promising approach. 6 Zirconium-based MOFs constructed using octahedral clusters exploit the strong Zr(IV)-O bonds between the metal centers and multitopic carboxylate linkers to yield robust materials that are stable in aqueous conditions. Moreover, they are free of labile -OH and -OH2 The zirconium-based MOF may have accessible metal sites that are covered with ligands, allowing for the adsorption of a variety of guest molecules. In one embodiment, the zirconium-based MOF is MOF-808, which has six binding nodes bridged by commercially available tritopic 1,3,5-benzenetricarboxylic acid linkers. 6 It is a cluster-based MOF.
[0038] 1A-C illustrate a zirconium-based MOF, namely MOF-808, according to one embodiment of the present invention. 6 cluster, Figure 1B illustrates the 1,3,5-benzenetricarboxylic acid linker, and Figure 1C illustrates the 6-linked MOF-808. MOF-808 is well suited for wastewater purification due to its high thermal and chemical stability (stable in solutions with pH 1-10). In the spn topology of MOF-808, of the 12 metal node binding sites, only 6 are occupied by the structural organic linker, and the remaining 6 can interact with adsorbed molecules, so a high uptake capacity of guest molecules can be expected.
[0039] The MOF-808 that can be used in the present invention has the molecular formula Zr 6 O 4 (OH) 4 (BTC) 2 (HCOO) 6 where BTC is 1,3,5-benzenetricarboxylic acid, and after acid washing and activation, has the molecular formula Zr 6 (μ 3 -O) 4 (μ 3 -OH) 4 (BTC) 2 (OH) 6 (H 2 O) 6 where BTC is 1,3,5-benzenetricarboxylic acid. Activation typically involves heating and vacuum drying to remove the solvent utilized during synthesis from the resulting MOF surface structure.
[0040] 2A-D illustrate analytical results for the synthesis of MOF-808 according to one embodiment of the present invention. MOF-808 can be synthesized and activated as follows: MOF-808 can be synthesized by activating ZrOCl in DMF with formic acid modulator at 120 °C. 2 8H 2 MOF-808 can be synthesized under solvothermal conditions using 97 mg of ZrOC in 7.5 mL each of DMF and formic acid. l2 8H 2 O and 63 mg H 3 The MOF was synthesized by combining BTC and 1,2-dichlorophenyltetrahydrofuran (1,2-dichlorophenyltetrahydrofuran). The resulting mixture was sonicated until the components were dissolved and placed in an oven at 120 °C to react for 72 h. The MOF was washed three times with fresh DMF (3x10 mL), soaked overnight in fresh DMF (10 mL), washed three times with acetone (3x10 mL), and soaked overnight in acetone (10 mL). The powder was then dried in a vacuum oven at 80 °C, and then soaked overnight in 10 mL of 0.1 M HCl to remove the formate capping ligands from the MOF nodes. The MOF was centrifuged to remove the HCl solution, followed by washing three times with water (3x10 mL) and three times with acetone (3x10 mL). (The acetone wash was performed to avoid structure stability issues related to capillary forces arising from repeated adsorption and desorption tests.) The MOF was soaked in acetone (10 mL) overnight, then dried in a vacuum oven at 80 °C for 1 h, and then activated in a Micromeritics SmartVacPrep at 120 °C for 20 h. 45.4 mg of sample was activated and used to collect the isotherm shown in Figure 2C.
[0041] To ensure that the six node sites are accessible for oxyanion adsorption, the as-synthesized MOFs are soaked in 0.1 M HCl to remove the formate capping ligands left by synthesis. Powder X-ray diffraction (PXRD) confirmed that the MOFs were phase pure and crystalline after removal of the formate capping ligands (Figure 2A shows the powder X-ray diffraction pattern of as-synthesized MOF-808 compared to the simulated pattern). 1 H NMR spectroscopy shows the disappearance of the formate proton at 7.92 ppm (Figure 2B). 2 Gas adsorption analysis was performed at 2020m 2 The as-synthesized MOF-808 has a Brunauer-Emmett-Teller (BET) area of 100 nm / g, pore sizes of 10 Å and 18 Å, and exhibits the expected type 1b isotherm (FIG. 2C shows the nitrogen adsorption-desorption isotherm of as-synthesized MOF-808 at 77 K along with the MOF-808 pore size distribution (inset)), consistent with previous reports. Scanning electron microscopy images show the expected morphology with a crystallite size of approximately 5 μm (FIG. 2D shows an SEM image of as-synthesized MOF-808 crystallites).
[0042] In one embodiment, MOF-808 was used to adsorb iodate. 2.5 mg of MOF-808 was exposed to a solution of potassium iodate with equivalent concentrations (41-287 ppm) exposing 2-7 iodate anions per metal node of the MOF. The MOF was immersed in the solution for 72 hours, resulting in uptake of between 0.95 iodates per node and 1.93 iodates per node for exposure of 2 and 7 iodate equivalents, respectively, as shown in Table 1 below. This translates to between 134 mg and 286 mg of iodates per gram of MOF-808, indicating that the MOF has a high gravimetric capacity for adsorption of iodates.
[0043] Table 1. Iodine uptake by MOF-808 [Table 1]
[0044] Figure 3A illustrates the kinetics for iodate adsorption using MOF-808 according to one embodiment of the present invention. The kinetics of the adsorption process were determined by exposing 2.5 mg of MOF-808 to 10 mL solutions of 1, 1.5, 2, 2.5, and 3 iodate anions per node (41, 61.5, 82, 102.5, and 123 ppm, respectively). The amount of iodate adsorbed (q) in mg per g of MOF was determined using Equation 1.
number
[0045] 3B illustrates a Langmuir plot of the adsorption of iodate on MOF-808 according to one embodiment of the present invention. The maximum adsorption capacity, Q, was calculated by fitting the data to the Langmuir adsorption model using Equation 2.
number
[0046] where Q is the equilibrium adsorption capacity (mg / g), C e is the equilibrium concentration (ppm), q e is the equilibrium uptake (mg / g), K L where Q is the Langmuir adsorption constant. Q was determined to be 233 mg / g. This is the highest gravimetric iodate uptake reported to date (e.g., for either MOFs or ion-exchange polymer resins), with maximum adsorption capacities exhibited by other materials ranging from 0.01 to 170 mg / g, as shown in Table 2.
[0047] Table 2. Various maximum adsorption capacities compared to MOF-808 [Table 2]
[0048] Based on the foregoing, MOF-808 adsorbs iodate, an oxyanion of iodine that is particularly difficult to adsorb. Therefore, MOF-808 can be used to adsorb other anion forms (e.g., I) by modifying the chemistry of the MOF nodes or linkers to incorporate typical anion exchange ligands (e.g., pendant ammonium cation molecules that can provide anion exchange functionality in aqueous solutions). - Thus, MOF Zr node clusters can physisorb iodate oxyanions, while surfaces within the cavities of the very same MOFs that incorporate, for example, ammonium chemistry features, can electrochemically retain anionic iodine.
[0049] FIG. 4A illustrates a density functional theory (DFT) optimized model of the MOF-808 node with bridging iodate ions, according to one embodiment of the present invention. FIG. 4B illustrates the simulated differential pair distribution function (dPDF) of the DFT model of FIG. 4A, the experimental dPDF data of MOF-808 loaded with iodate, and the simulated dPDF with unbound iodate, according to one embodiment of the present invention. FIG. 4C illustrates the diffuse reflectance infrared Fourier transform spectroscopy data of untreated and iodate-loaded MOF-808. Specifically, FIG. 4A illustrates the DFT optimized model of the MOF-808 node with bridging iodate ions, with hydrogen atoms omitted for clarity. FIG. 4B illustrates the model simulated dPDF (as shown in the separate line trace at the top) of the DFT model of FIG. 4A, which shows the η 2 μ 2Figure 4B also shows the dPDF (from synchrotron X-ray total scattering measurements) of iodate-loaded MOF-808 (variable width traces shown below the top discrete line trace of the DFT model) and the dPDF of untreated iodate (lower discrete line trace).
[0050] As shown, at 3674 cm after iodate loading -1 The significant reduction in OH stretching at 100 nm confirms that the -OH ligands have been replaced by iodates (Figure 4C). The distances obtained by dPDF analysis indicate that the Zr 6 These distances are consistent with those determined by density functional theory (DFT) calculations on the optimized geometry of the cluster. After loading of iodate, atom pair distances of 1.9 and 3.7 Å are observed, corresponding to IO and Zr-I, respectively. This signal is consistent with the bonding mode in which iodate bridges two adjacent zirconium metal centers in the cluster, or η 2 μ 2 This is consistent with a bonding mode. The peaks at longer distances are consistent with the expected distance between the iodine in the cluster and the next further zirconium metal center. The DFT calculations suggest that hydrogen bonding with the bound water has a directional effect on the orientation of the iodates - thus the portion of the dPDF not clearly indexed by the model could plausibly arise due to dispersed orientation, for example by interactions with the further water layer.
[0051] FIG. 5A illustrates a DFT-optimized model of a MOF-808 node with bridging iodate ions, according to another embodiment of the present invention. FIG. 5B illustrates the dPDF of the DFT model of FIG. 5A, experimental dPDF data for iodate-loaded MOF-808, and a simulated dPDF with unbound iodate, according to one embodiment of the present invention. Specifically, FIG. 5A illustrates the dPDF of MOF-808 Zr 6The optimized structural model of two bridged iodate anions bound to opposite sides of a node is shown in Figure 5B. The model simulated dPDF of the DFT model of Figure 5A (shown as separate line traces at the top). Figure 5B also shows the dPDF of iodate-loaded MOF-808 (varying width traces shown below the separate line traces at the top of the DFT model) and untreated iodate (separate line traces at the bottom).
[0052] FIG 6A shows a DFT optimized model of a MOF-808 node with bridging iodate ions according to another embodiment of the present invention. FIG 6B shows a simulated dPDF of the DFT model of FIG 6A, experimental dPDF data of MOF-808 loaded with iodate, and a simulated dPDF with unbound iodate according to one embodiment of the present invention. Specifically, FIG 6A shows the Zr 6 Optimized structural models of the bridged iodate anion bound to the node are shown in Figure 6B. Model simulated dPDFs of the DFT model of Figure 6A (shown as separate line traces at the top). Figure 6B also shows the dPDFs of iodate-loaded MOF-808 (variable width traces shown below the separate line traces at the top of the DFT model) and untreated iodate (separate line traces at the bottom).
[0053] FIG 7A illustrates a DFT optimized model of a MOF-808 node with bridging iodate ions according to another embodiment of the present invention. FIG 7B illustrates the simulated dPDF of the DFT model of FIG 7A, experimental dPDF data for iodate-loaded MOF-808, and a simulated dPDF with unbound iodate according to one embodiment of the present invention. Specifically, FIG 7A illustrates the simulated dPDF of the Zr ions on opposite sides of a two-node MOF-808 system. 6Figure 7B shows an optimized structural model of two bridged iodate anions bound to nearest neighbor sites on a node. Figure 7B shows the model simulated dPDF of the DFT model of Figure 7A (shown as separate line traces at the top). Figure 7B also shows the dPDF of iodate-loaded MOF-808 (variable width traces shown below the separate line traces at the top of the DFT model) and untreated iodate (separate line traces at the bottom).
[0054] FIG. 8A illustrates a DFT-optimized model of a MOF-808 node with bridging iodate ions, according to another embodiment of the present invention. FIG. 8B illustrates a simulated dPDF of the DFT model of FIG. 8A, experimental dPDF data for iodate-loaded MOF-808, and a simulated dPDF with unbound iodate, according to one embodiment of the present invention. Specifically, FIG. 8A illustrates the simulated dPDF of the Zr ions on opposite sides of a two-node MOF-808 system. 6 Figure 8B shows an optimized structural model of two bridged iodate anions bound to the next-nearest neighbor sites on a node. Figure 8B shows the model simulation dPDF (shown as separate line traces at the top) of the DFT model of Figure 8A. Figure 8B also shows the dPDF of iodate-loaded MOF-808 (traces of varying widths shown below the separate line traces at the top of the DFT model) and untreated iodate (separate line traces at the bottom).
[0055] " 2 " indicates the fact that two adjacent oxygen atoms in the iodate are adsorbed atoms, and "μ 2It should be understood that "adjacent" refers to an adsorption site on the MOF surface that is two adjacent Zr metal atoms. In the case of oxygen, "adjacent" refers to one oxygen on either side of the included iodine atom, and in the case of Zr, "adjacent" refers to two Zr atoms separated by sufficient space to bond two adjacent oxygens. It should be understood that this space can be comprised of organic components of the MOF node features, and those Zr atoms are held either within the same node structure or within two adjacent node structures in equilibrium within the distance required to bond iodate oxygens. The unexcluded space in both choices allows unhindered access from liquid aqueous solutions to the adsorption site, or two Zr atoms on one node, or two Zr atoms appropriately positioned to pick up iodate using two nodes (one Zr atom from each node). It should also be understood that the hexagonal symmetry of the macrocrystal that gives the unit cell six filled node structures pendant allows for adsorption to iodate (and other oxyanions similar) without being hindered by linker excluded volume.
[0056] FIG. 9A illustrates powder X-ray diffraction patterns of various forms of MOF-808, according to one embodiment of the present invention. Specifically, the X-rays in the bottom pattern are for simulated MOF-808, and the pattern immediately above is for iodate-loaded MOF-808 (CuKα, λ=1.54178 Å). These data confirm that MOF crystallinity is maintained after iodate adsorption. It should also be understood that the X-ray patterns shown for various concentrations of HCl illustrate that MOF crystallinity is maintained even after three regeneration wash steps with 1, 3, 5, or 10% HCl. (Regeneration is discussed further below.)
[0057] 9B illustrates isotherms of various forms of MOF-808, according to one embodiment of the present invention. Specifically, the top two isotherms, which trace substantially over one another, are adsorption / desorption isotherms of untreated MOF-808, while the bottom two lower isotherms, which also trace over one another, are adsorption / desorption isotherms of MOF-808 after adsorption or loading with iodate. The isotherms are shown at 1860 m 2 / g to 1270m 2 Reduction of BET area to 0.75 cm / g 3 / g to 0.51cm 3 It should be noted that this is a type 1b isotherm with a decrease in pore volume to 1000 / g. These data confirm that the MOF remains porous after iodate adsorption. It should also be noted that the MOF remains porous even after regeneration, as shown by the two middle isotherms. After regeneration, the surface area is 1850 m 2 / g, pore volume is 0.75 cm 3 (Regeneration is discussed further below.)
[0058] 10A-10D show SEM images and SEM-EDS line scan analysis of iodine, zirconium, and MOF-808 crystallites according to one embodiment of the present invention. Larger MOF-808 crystallites were grown for easier visualization by electron microscopy. Scanning electron microscope (SEM) images show that the expected morphology of MOF-808 is maintained after iodate loading. Furthermore, energy dispersive X-ray spectroscopy (EDS) elemental mapping and line scan analysis of iodate-loaded MOF-808 crystallites show that iodine is uniformly distributed throughout the MOF crystallites.
[0059] Depending on the envisioned application, the ability to reuse and recycle the sorbent material can be an important factor, reducing the cost and amount of material required for the remediation of contaminated water. To evaluate the reusability of MOF-808, 10 mg of MOF-808 was loaded with iodate by exposing the MOF to a 1148 ppm potassium iodate solution overnight, resulting in an uptake of 1.36–1.61 iodate per node. The next day, the iodate-loaded MOF-808 in iodate solution was placed on the membrane filter of a glass microfiltration apparatus, and the flask was subjected to a vacuum treatment to filter the solution. The MOF-808 powder was then washed three times with 10 mL of water. Then, 10 mL of 1%, 3%, 5%, or 10% HCl was passed through the MOF by controlled suction filtration over a period of 5 min. The MOF was then washed three times with water and placed overnight in 10 mL of fresh 1148 ppm iodate solution. When a 1% HCl solution was used to regenerate MOF-808, a maximum of 0.40 iodates per node were removed from the MOF, although performance improved with increasing acid strength.
[0060] 11A-D illustrate the iodate adsorption and desorption cycles of MOF-808 according to one embodiment of the present invention. Washing the MOF with 3% HCl (FIG. 11B) revealed that up to 0.55 iodates per node were removed, and using 5% HCl (FIG. 11C) further increased this to 1.15 iodates per node. Using 10% HCl (FIG. 11D) yielded maximum removal, with up to 1.43 node equivalents removed, representing up to 85% removal of the adsorbed iodate from the MOF. Between each acid wash, MOF-808 was exposed to a 1148 ppm potassium iodate solution, and in both cases, maximum iodate uptake was maintained over the next two adsorption-desorption cycles.
[0061] It should also be understood that modifications can be made to the MOF, such as MOF-808. Since there are established chemistries in the literature for modifying the linker moiety of MOFs, such as SALE (solvent-assisted linker exchange) and SALI (solvent-assisted ligand incorporation) (see, for example, P. Deria, W. Bury, JT Upp, OK Farha, “Versatile Functionalization of the NU-1000 Platform by Solvent-Assisted Ligand Incorporation,” Chem. Commun. 2014, 50, 1965-1068, and P. Deria, JE Mondloch, O. Karagiardi, W. Bury, JT Upp, OK Farha, “Beyond Post-Synthesis Modification: Evolution of Metal-Organic Frameworks via Building Block Replacement,” Chem. Soc. Rev., Chem. Soc. Rev., 2014, 43, 5896-5912), one skilled in the art can apply such chemistries to introduce appropriate ligand functionalities into the cavity of MOF-808 and chloride (Cl - ), iodide (I - ), and selenate (SeO 3 2- ), selenite (SeO 3 2- ), antimonate (SbO 3 - ), antimonite (SbO 2 - ), lead oxide (Pb(OH) 6 2- , Pb(OH) 6 4- , PbO 3 2- , and PbO 2 2- ), and sulfuric acid (SO 4 2-), to increase the overall binding capacity of the material for these analyte species, and therefore to improve the engineering of these media for water treatment functions. In the particular case of selenates or selenites, one of the linker chemistries predicted by those skilled in the art of theoretical binding calculations is functionalized urea chemistry, such as pyridyl urea, held pendant on linear carbon or ether oxygen chains of sufficient length (e.g., 6 to 12 elemental carbon or oxygen atoms in length) with suitable terminal groups for attachment to the cavity and hole forming components of the MOF, so as to allow the urea-derived ligands to contact the selenium oxyanions penetrating the MOF cavities.
[0062] In use and in accordance with one embodiment of the present invention, the MOFs of the present invention can be used to selectively remove specific species from liquid streams. In particular, MOF-808 has the following properties: 129 I, 131 I, iodide (I - ), iodate (IO 3- ), and of note, 129 I and 131 I is usually converted to iodide (I - ) and iodate (IO 3- In some embodiments, to achieve removal of a given species from a liquid or liquid stream, a certain amount of MOFs and a structure to hold the MOFs or a structure to which the MOFs are attached and that allows contact between the liquid and the liquid stream and the MOFs are required.
[0063] In general, it should be understood that the amount of MOF required depends on several factors. For example, the Langmuir adsorption capacity (moles of ion per unit weight of MOF) can be obtained for a particular analyte to be removed (e.g., iodate oxyanion containing iodine) and, in conjunction with the influent concentration of the stream or analyte to be treated, the amount of MOF required to contact the liquid stream or influent stream, for example, on the bed of a desalter associated with a nuclear power plant, such as a coolant washing system, or on the membrane of a powdered resin retention filter desalter. Other factors include sufficient contact of the liquid stream and the MOF on the substrate, which may depend on the geometry or design of the corresponding device used for contact between the liquid stream and the MOF, and there may be loss of MOF during loading or unloading of any substrate, such as loading or unloading of beads in the desalter or other device used. It should be understood that in the case of a desalter, the desalting beads may be a mixture of beads or a mixed bed of beads containing beads for both removal of cations (e.g., by ion exchange) and removal of anions (by MOF). In this case, the amount of contact between the liquid stream and the MOF beads in particular also needs to be specifically considered when determining the amount of MOF beads to use.
[0064] Furthermore, in the case of filter desalination apparatuses where powdered ion exchange resins are typically held on the membrane pleats (e.g., in reactor water purification systems (RWCUs) for aqueous reactor coolants in boiling water reactor (BWR) nuclear power plants), the MOF crystallites themselves can be placed on these pleats either alone or in combination with powdered ion exchange resins (e.g., sulfonic acid functionalized cation exchange polystyrene divinylbenzene (PS / DVB) polymer network resins). In this case, the hydrodynamic forces provided by the water flowing through the membrane pleats can aid in embedding the MOF media directly into the high pressure side of the filter desalination apparatus. In this case, the described MOFs can act as anion purification media, as a counterpart to the powdered cation exchange resin. The amount of contact between the liquid stream and the MOF crystallites themselves must also be considered in determining the amount of MOF to be used.
[0065] A particular MOF can be attached to any structure or substrate that is used to facilitate contact between the MOF and a liquid stream having a particular species to be removed. It should be understood that the structure or substrate can be any substrate to which a given MOF can be attached and is suitable for use in an environment or process that can be used to remove a particular species or compound from a liquid or liquid stream. In some embodiments, the substrate can be an inert substrate to avoid any chemical interaction with the liquid or liquid stream being treated. In some embodiments, the substrate has a physical shape that can be placed and used in a given process or a particular processing device to remove a particular species from a given liquid stream.
[0066] For example, the MOFs can be installed in a pre-coatable filter / desalter (as described above for the nuclear power plant coolant cleaning application) or in a separate packed column, including those already in use in a given facility or plant (e.g., existing vessels used for ion exchange). For example, the MOFs can be pre-coated onto the filter fabric of an existing filter desalter or similar filter system. The structure can then be appropriately installed to allow contact between the liquid flow and the MOFs on the structure. For example, using a MOF-coated desalter or similar filter, the liquid or water to be treated can flow through the filter fabric, e.g., from the outside of the cylindrical filter through the filter fibers into the lumen, allowing contact between the MOFs and the water. Once in contact with the liquid flow, the particular species to be removed is adsorbed onto the MOFs, thereby reducing the concentration of that species in the liquid flow.
[0067] In some embodiments, the substrate may be a single bead or multiple beads. In some embodiments, the beads may be beads of an inert polypropylene polymer resin. In some embodiments, the substrate may be a macroscopic fabric, such as a mesh material or a mesh filter. In some embodiments, the substrate may be a molecular fabric made from organic strands, consisting essentially of a two-dimensional copolymer structure or an organic woven material. In some embodiments, the substrate may be a pleated media filter constructed from a metal or ceramic-based material to which the MOFs adsorb.
[0068] It should be understood that the following description of the method of attaching a given MOF to a substrate, as well as the description of the method of using a substrate having an attached MOF, generally refers to MOFs. However, it should be understood that in all embodiments described herein, the specific MOFs described above may be used, such as MOF-808. Thus, while some of the specific MOFs described above are capable of or configured to remove specific liquid-phase anion species, it should be understood that other MOFs capable of removing other liquid-phase species from a liquid or liquid stream may be used and attached to a given substrate as well. Furthermore, while the following methods are described with reference to specific substrates, it should be understood that other substrates, including substrates having different chemical compositions or substrates having different geometric shapes, may be used in any combination with any suitable MOF.
[0069] In general, the method of attaching a given MOF particle to a substrate may depend on the particular substrate used. Thus, methods are described below for attaching a given MOF, including any applicable MOF, as well as NU-1000 and MOF-808, to beads, including a plurality of beads, to macroscopic fabrics, such as mesh fabrics or mesh filters, and to molecular fabrics made of organic strands, consisting essentially of two-dimensional copolymer structures or organic woven materials.
[0070] In some embodiments, a given MOF may be attached to a substrate that is a bead or a plurality of beads. In some embodiments, the beads may be inert polypropylene polymer resin beads. In some embodiments, the beads may be selenite (SeO 3 2- ) and selenate (SeO 4 2- oxyanions of selenium, including Sb[III] (antimonite) or Sb[V] (antimonate), and Pb(OH) 6 2- , Pb(OH) 64- , PbO3 2- , PbO 2 2- Lead oxyanions, including oxyanions of either Pb[II] or Pb[IV] in their redox state, such as sulfate (SO 4 2- ), and IO 3- It is used to remove anions, including oxyanions of iodine such as iodate.
[0071] Generally, the method of attaching MOFs is performed using a buffer modifier that adheres the MOFs to the surface of the beads. In some embodiments, the buffer modifier can be a buffer modifier typically used in capillary electrophoresis, such as an osmotic flow modifier, including cetyltrimethylammonium bromide (CTAB) and beta-cyclodextrin (beta-CD). Both CTAB and beta-CD are compounds that bind well to MOF particles at room temperature and chemisorb the MOFs to the surface of the beads.
[0072] In one embodiment, CTAB may be used to attach MOFs to bead surfaces. In this case, atomic layer deposition (ALD) is used to seed beads with metal oxides that provide surface hydroxyl groups that can form chemical bonds with MOF particles via CTAB. In some embodiments, metal oxides chemisorb to the bead surface in water, thereby making the hydroxyl groups available for attachment to CTAB, for example, via the cationic head groups of CTAB. These metal oxides include, but are not limited to, aluminum oxide, titanium oxide, zinc oxide, and combinations thereof. When exposed to water, the deposited metal oxides appear to resemble silicon dioxide / surface hydroxides in capillary electrophoretic osmotic flow reversal applications of CTAB. Thus, the MOFs are then attached to CTAB through hydrogen bonds, electrostatic interactions, and van der Waals induced dipole-dipole forces. Without being limited by theory, the non-polar surface of the MOF, such as the organic linker of the MOF, may attach to the trimethyl "arms" of CTAB.
[0073] In one embodiment using CTAB, a substrate (such as beads) may first be subjected to ALD and the metal oxide may be chemisorbed to the surface of the beads. Alternatively, CTAB and MOFs may be combined at room temperature to attach the MOFs to CTAB and form a solution of MOF-attached CTAB. The beads with attached metal oxides may then be contacted with the solution or combined with CTAB having attached MOFs to obtain CTAB attached to the bead surface via the metal oxide, again at room temperature in an aqueous solution, and in some embodiments in a basic aqueous solution. Alternatively, the beads after being subjected to ALD to attach the metal oxide may be mixed with an aqueous solution containing MOFs, and in some embodiments, a basic aqueous solution containing MOFs. CTAB may then be added to the solution, attaching to both the MOFs and the metal oxide, resulting in the attachment of the MOFs to the bead surface. The beads may then be washed and dried. Thus, at this point, MOF-adsorbed beads, such as a plurality of MOF-adsorbed polypropylene beads, have been produced and may constitute a commercial product that can be used as described further below.
[0074] In another embodiment, MOFs may be attached to the bead surface using beta-CD. In this case, the substrate does not need to be subjected to ALD. Rather, the non-polar regions of beta-CD attach to corresponding non-polar sites on the polypropylene bead via hydrogen bonding, electrostatic interactions, and van der Waals induced dipole-dipole forces. The MOFs can then be attached to the beta-CD via interactions between one or more polar moieties on the surface of the MOF due to the negative charges on the beta-CD. In some embodiments, the MOFs can be attached to the beads in an aqueous solution containing beta-CD. In some embodiments, a less polar solvent such as an alcohol may be used. The beads can then be washed and dried. Thus, at this point, MOF-adsorbed beads, such as multiple MOF-adsorbed polypropylene beads, have been produced and may constitute a commercial product that can be used as further described below.
[0075] It should be understood that in some embodiments, both beta-CD and CTAB may be used in combination, in which case the substrate or beads may be subjected to ALD, after which a solution containing the MOF and both CTAB and beta-CD may be added.
[0076] It should also be understood that in some embodiments, the surface of the beads for functionalization with CTAB and beta-CD may be silicon dioxide. In some cases, polymer beads may be functionalized using silane hydroxide chemistry to accept silicon appendages, and then accept hydroxide to provide the necessary chemistry to attach CTAB or beta-CD.
[0077] It should be understood that in some embodiments, the ion exchange resin beads are polystyrene divinylbenzene crosslinked (2-12%) copolymer beads functionalized within the pores by chemical attachment of exchange ligands to pendant benzyl rings from the polymer backbone. In such cases, replacing the MOF coated substrate beads and achieving adequate water washing of the anion beads from the mixed bed requires matching the density of the latter beads to the anion exchange resin beads. Furthermore, there are several options for polypropylene depending on the local stereochemistry of the propylene adduct in the free radical polymerization process.
[0078] Thus, in some embodiments, the process of preparing a suitable number of beads for use, for example, in the deep bed of a plant desalter includes determining the specific gravimetric capacity of the MOF for the analyte / oxyanion of interest; calculating the amount of MOF that needs to be associated with each bead, thereby allowing an assessment of the number concentration of MOF-coated beads in water already present in the process stream that must be flushed into the existing deep bed of the desalter; testing the equilibrium density with existing anion exchange beads in the deep bed of the plant desalter and investigating the possibility of exchange between those beads and the MOF-coated beads via typical plant sluicing methods; and adjusting the number concentration of MOF-coated beads to account for lost beads in the previous steps.
[0079] In another embodiment, the invention includes a method of attaching MOFs to a macroscopic fabric for later use. In some embodiments, the macroscopic fabric can be any fabric, including man-made fiber-based materials, to which a given MOF can be attached. In some embodiments, the macroscopic fabric is a mesh material or mesh filter, including an inert polypropylene-based mesh material or filter. It should therefore be understood that the fabric may have any dimensions, such as any area or surface area, as desired or dictated by the final use of the fabric. MOF particles may be attached to the fibers of the fabric in the same manner as previously described for attachment to beads. It should therefore be understood that buffer modifiers such as beta-CD and CTAB may be used as described above to attach MOFs to the fabric in combination with ALD processing of the fabric. After attaching MOFs to the macroscopic fabric, a MOF-adsorbed macroscopic fabric has been produced and may constitute a commodity that can be used as further described below. It should be understood that the term "macroscopic" is used to distinguish this fabric as one that can be seen by the naked eye or physically handled by hand, as opposed to the molecular fabrics described below.
[0080] In another embodiment, the invention includes a method for attaching MOFs to a molecular fabric for subsequent use. In some embodiments, the molecular fabric is made from organic strands that essentially form a two-dimensional copolymer structure or organic woven material to which a given MOF can be attached. MOF particles can be attached to the strands of the fabric in the same manner as previously described for attachment to beads. It should therefore be understood that buffer modifiers such as beta-CD and CTAB may be used as described above to attach MOFs to the fabric in combination with ALD processing of the fabric. After attaching MOFs to the molecular fabric, a MOF-adsorbed molecular fabric has been produced and may constitute a commodity that can be used as further described below. It should be understood that the molecular fabric is a fabric formed at the molecular level and is therefore much smaller in size than, for example, the macroscopic fabrics described above.
[0081] Once attached, as described above, a substrate with attached MOFs, such as MOF-808, can be used to remove specific chemical species from a liquid or liquid stream, such as an industrial liquid stream (e.g., a power plant coolant stream, such as a nuclear power plant stream) or a wastewater stream. In general, a substrate with attached MOFs can be positioned to allow contact between a liquid containing one or more liquid species to be removed from the liquid and the MOF. Upon contact, the liquid species to be removed attaches to the MOF and can thus be removed from the liquid. In this regard, the manner in which a substrate with attached MOFs can be used depends on the particular attached MOF and the liquid phase species it can remove, as well as the physical configuration of the inert substrate used (e.g., beads or fabric). However, it should be understood that any method or device that provides or allows contact between the MOF and the liquid can be used.
[0082] In the case of beads, they can be used in the same manner as conventional resin beads, for example, to remove certain chemical species from a liquid by placing the beads in a resin bed in a given vessel through which the liquid to be treated can pass. It should be understood that existing equipment designed to manage resin beads can be adapted to manage the use of beads coated with MOF particles, if necessary. In one embodiment, a cylindrical vessel containing a bed of beads coated with MOF particles can be used. In this case, the bed of beads can be stationary in the vessel and a liquid flow can pass through the vessel, thereby passing through the bed of beads and bringing into contact between the liquid containing the liquid species to be removed and the MOF particles. Upon contact, the liquid species to be removed can attach to the MOFs and thereby be removed from the liquid passing through the vessel.
[0083] It should be understood that in some embodiments where the vessel contains resin beads used to remove a particular liquid phase species, such resin beads can be replaced by beads coated with a given MOF according to the present invention. In one embodiment, if a resin bead needs to be replaced, it can be easily replaced in the same equipment with a bead coated with a given MOF according to the present invention. Alternatively, the resin beads can be replaced with inert polypropylene beads, and the attachment of the selected MOF can be performed in-situ. In this case, the beads can be pre-treated with ALD to attach the given metal oxide and then placed in the vessel, or the treatment with ALD to attach the metal oxide can also be performed in-situ. In the latter case, the beads can be placed in the vessel and then treated using ALD to attach the metal oxide. Then, a solution containing CTAB and the selected MOF can be added to the vessel, or a solution of CTAB can be added to the vessel and then a solution of the selected MOF can be added to the vessel to attach the CTAB and MOF to the beads. As a result, the original resin beads can be replaced with beads coated with the selected MOF without modifying or changing any of the existing equipment used for the original resin beads.
[0084] Alternatively, the beads can be placed in a vessel and then a solution containing beta-CD and the selected MOF can be added to the vessel to attach the beta-CD and MOF to the beads, or a solution of beta-CD can be added to the vessel and then a solution of the selected MOF can be added, such that the original resin beads can be replaced with beads coated with the selected MOF without modifying or changing any of the existing equipment used for the original resin beads.
[0085] In the case of macroscopic fabrics coated with selected MOFs, such fabrics can be positioned or arranged to allow a liquid flow to pass through the fabric, thereby resulting in contact between the liquid containing the liquid species to be removed and the MOF particles attached to the fibers of the fabric. Upon contact, the liquid species to be removed attaches to the MOFs and is thereby removed from the liquid passing through the fabric. It should be understood that the fabric can be placed inside a vessel or pipe or any piece of equipment such that the liquid passes through the fabric.
[0086] In one embodiment, a desalter through which liquid flows may be used. In this case, the macroscopic fabric is a mesh filter that can be spirally rolled, thereby creating a lumen in the center. The liquid may pass into the desalter and around the outside of the rolled mesh filter. The liquid may then pass through the rolled mesh filter, into the lumen or center of the desalter, and out of the center of the desalter. It should be understood that in some embodiments, an existing mesh filter may be coated with the selected MOF. In this case, the MOF may be attached in situ to the existing mesh filter in the same manner as described above for in situ coating of beads in an existing container.
[0087] It should also be understood that MOF-coated fabrics may be used in many different situations. In one embodiment, MOF-coated fabrics may be used on top of a resin bed to facilitate removal of liquid-phase species, provide either removal of other liquid-phase species relative to those removed by the resin bed, or additional removal of the same or similar species. Furthermore, in an embodiment in which a bed of beads is coated in situ with a selected MOF, it should be understood that the use of macroscopic fabrics on top of the bed may be coated in situ with the selected MOF at the same time as coating the bed of beads. Thus, it should also be understood that the MOFs used for the beads and fabric may be the same or different, and in the different cases, it may be necessary to coat either the beads or the fabric before placing them in a given container.
[0088] In the case of molecular fabrics coated with selected MOFs, such fabrics can be positioned or arranged so that a liquid flow passes through the fabric, thereby resulting in contact between the liquid containing the liquid species to be removed and the MOF particles attached to the fibers of the fabric. Upon contact, the liquid species to be removed can attach to the MOFs and thereby be removed from the liquid passing through the fabric. It should also be understood that the fabric can be placed inside a vessel or pipe or any piece of equipment such that the liquid passes through the fabric. It should also be understood that the molecular fabric can be generated in situ and then the selected MOF particles are attached. In some embodiments, the molecular fabric can be constructed to be located at the outlet of a vessel, such as a vessel containing resin beads in a bed or a desalter.
[0089] While the MOFs of the present invention may be used in such liquid flow applications in their native structure, the amount of pressure required to infiltrate a packed bed of such small particles (typical sizes range from 75 to 1200 nanometers, forming 5 micron crystallites from the MOF particles) may exceed available fluid drive equipment, meaning that it may be necessary to transfer the MOF particles to some other larger particle carriers (larger than the order of resin particles, typically 50 to 850 micron diameter in powder or bead form) so that the fluid can more easily infiltrate into the collection of carrier particles. Any methodology can be used to contact the MOF particles with suitable carrier particles, so that the permeability of the collection of such carrier particles can provide the required throughput of fluid volumes, either in a cylindrical flow through a bed of such carrier particles or through a filter that provides a porous surface on which such carrier particles are coated. Thus, the adsorption properties of the MOFs are still evident as the MOFs themselves are exposed to the analyte in the water stream flowing around the carrier particles with the MOF media attached.
[0090] However, regardless of the substrate used, it should be understood that for a given liquid flow and the concentrations of the various liquid phase components to be removed, the capacity of the MOFs selected to remove those liquid phase components is generally much greater, so there is no limit to MOF saturation. Thus, for example, rather than using a bed filled with MOF particles, using a substrate coated with MOF particles still provides the requisite surface area to obtain the desired removal of a given liquid phase species.
[0091] Once removal of the desired species from a given liquid or liquid stream has occurred, regeneration of the MOF may be performed as needed. In general, regeneration of a given MOF may be performed to remove the adsorbed species from the MOF, thereby allowing reuse of the MOF. Those skilled in the art will understand that the MOF requires regeneration or has been consumed, depending on the change in the performance of the MOF over time or the removal of the adsorbed species from the liquid. Tests to determine the change in removal rate, or tests of samples of the MOF to determine the saturation level of the adsorbed species on the MOF, may be performed to determine whether regeneration is appropriate.
[0092] Regeneration of MOFs can be accomplished using chemical washes or rinses. For example, adsorbed anions can be removed by acid treatment, such as, but not limited to, hydrochloric acid, sulfuric acid, or nitric acid washes. Subjecting MOFs to such treatments results in the adsorbed species being collected in a solution used to regenerate the MOF, which can be further processed as needed. At this point, the MOFs can be ready for reuse.
[0093] Depending on the structure to which the MOF is attached or the medium to which it is attached, the equipment used for regeneration may vary. In industrial applications, including reactor coolant kidney wash loops in nuclear power plants, regeneration procedures may be utilized for the attached MOF, which means including a substrate implanted in the process equipment. The crystallites of the separated MOF may regenerate themselves according to the procedure described above for acid regeneration with various concentrations of aqueous HCl, which may reach up to about 10%, and maintain their adsorption capacity and porosity after regeneration. Then, when regenerated, the MOF may be deployed again for use. Thus, it should be understood that depending on the substrate used to support the MOF, the MOF may be regenerated in situ or removed from a given process and regenerated and returned to use in the process.
[0094] In one embodiment, as previously described, MOF-808 can be regenerated using a hydrochloric acid wash. Referring to Figures 11A-D, varying the concentration of HCl results in varying amounts of removal of the adsorbed species, in this case iodate. One of skill in the art can determine the concentration of any acid wash to result in the desired removal of the adsorbed species from the MOF.
[0095] In particular applications in reactor coolant purification media, MOFs for removing iodates may actually provide for the continued and safe operation of nuclear power plants where fuel cladding metal leaks are detected during normal power generation operations. Typical polymer-based anion exchange resins are incapable of removing radioactive iodates from water at low concentrations; in particular, they slough iodates from the resin media back into the purification loop effluent due to equilibrium constraints on the filtrate effluent concentration. On the other hand, MOFs such as MOF-808 have the potential to retain iodates more strongly and therefore to reduce effluent concentrations to approximately less than 10 ppb.
[0096] In the case of boiling water reactors (BWRs), defects in the fuel cladding can result in the release of iodine gas from inside the fuel rods. This radioactive iodine is usually produced in the nuclear fuel during operation by nuclear activation of xenon inside the pressurized fuel rods. When released into the coolant water, under oxidizing conditions produced by radiolysis, this iodine is oxidized to iodates, which must be removed from the reactor water for continued operation. Thus, the capture of these low concentrations of radioactive iodates using MOFs can result in the continued safe operation of BWR nuclear cores because in BWRs, control blade operation along with off-gas gamma scanning can be used to isolate collection areas where fuel cladding leaks are occurring. Although the ultimate cause of the cladding metal defect is varied (such as debris impact, hydrogen embrittlement and crack initiation, thermal transients, or other reasons such as grid-to-rod fretting), in the example of a suitable small defect, the solution that gives continued operation is, first, to be able to isolate and suppress the fission reaction in the leaking assembly (using an independent control blade arrangement in the BWR core) and, second, to be able to continuously clean the radioactive iodates added to the coolant by the leaking rod. If these two conditions are met (the latter using MOFs according to the present invention), the plant can continue to operate until the planned end of the power cycle, if the core is rebuilt anyway by replacing parts of the assembly with new fuel. In that example, the leaking assembly can be removed during a refueling outage as well, before the BWR can be restarted. This is much more economical than being forced to shut down the reactor before the planned refueling outage to find and remove a small leaking assembly, causing a mid-cycle rebuild of the core before the plant can be restarted. Therefore, the use of MOFs in cleaning according to the present invention is essential to enable this type of continuous full cycle operation in BWRs. Furthermore, the BWR RWCU system utilizes a filter demineralizer that can be directly deployed without the need for an additional substrate to implant MOF crystallites.
[0097] Similar fuel leaks can occur in pressurized water reactors (PWRs), but PWRs have a lower ability to detect and isolate neutronic fuel leaks, given that the control rod design does not provide for partial and independent insertion as in BWR designs. Thus, when a leak is detected, PWRs usually need to perform a mid-cycle shutdown to find and remove the problematic fuel assemblies (by sipping them in a spent fuel pool). As with BWRs, the degree to which radioactive iodates can be controlled in the reactor water cleaning loop can be beneficial to personnel exposure doses if refueling operations are ongoing during a mid-cycle shutdown. Nevertheless, the degree to which released iodine gas is oxidized to iodates can be altered by the shutdown operation of the PWR reactor coolant as well. Ultimately this can be mostly off-gas, or aqueous iodates, for which the bead-supported MOFs according to the present invention can be applied for cleaning purposes. Determining factors include the manner and rate at which hydrogen is removed during the shutdown transients as the plant enters the intermediate cycle shutdown period, and the degree of coolant overoxidation during the PWR intermediate cycle transients planned for each PWR. In general, individual plants are constrained by their technical specifications as to the degree of freedom that PWRs may have for restarting with high concentrations of radioactive iodates or fuel leakage in the primary reactor coolant circuit. EXAMPLES
[0098] Experimental Methods Maximum iodate uptake per node. 2.5 mg of activated MОF-808 was placed in a 15 mL centrifuge tube with 10 mL of potassium iodate solution at either 41, 82, 123, 164, 205, 246, or 287 ppm. These correspond to exposure of 2, 3, 4, 5, 6, and 7 iodate anions per metal node of the MОF. After 72 h, the solution was centrifuged to precipitate the MОF. A 50 μL aliquot was taken and diluted to 5 mL with 0.5% ammonium hydroxide. The iodine concentration of each sample was measured by ICP-MS and compared to that of the corresponding stock solution to measure iodate uptake by the MОF. The iodate samples contained volatile iodate that can permeate polypropylene and cause memory effects and inaccurate concentration measurements. 2 A base matrix is required to prevent the formation of
[0099] Iodine uptake kinetics. Iodine uptake kinetics. 2.5 mg of activated MOF-808 was placed in a 15 mL centrifuge tube with 10 mL of potassium iodate solution at either 41, 61.5, 82, 102.5 or 123 ppm. These correspond to exposure of 1, 1.5, 2, 2.5 and 3 iodate molecules per node of the MOF. The solution was centrifuged for 3 min to precipitate the MOF, after which aliquots of the supernatant were taken at 4, 6, 8, 10, 20, 40, 60, 120 and 180 min and 24, 48 and 72 h after the initial exposure. Iodine concentration was measured by ICP-MS. Samples were diluted 100-fold with 0.5% ammonium hydroxide solution by adding 50 μL aliquots to 5 mL.
[0100] The amount of adsorption (q), in mg / g, was determined for each exposure concentration using Equation 1. The maximum equilibrium adsorption capacity (Q) was determined by fitting the data to the Langmuir adsorption model. The Langmuir equation (Equation 2) was used to determine Q for iodate uptake in MOF-808, where C e is the equilibrium adsorption concentration (ppm), calculated as the average concentration at 48, 72, and 96 hours, and q eis the equilibrium uptake (mg / g), determined as the average of the calculated q values at 48, 72, and 96 h.
[0101] Powder X-ray diffraction (PXRD). Powder X-ray diffraction (PXRD) patterns were collected on a Bruker D8 Advance diffractometer (measured in the range 3°<2θ<40°, step 0.02°, scan speed 0.200 s) equipped with a LYNXEYE linear position sensitive detector (Bruker AXS, Madison, WI). Suitable samples were applied directly to silicon wafers in a proprietary low background sample holder. Data were collected with continuous coupled θ / 2θ scans using Ni filtered CuKα (radiation with λ=1.54178 Å, operated at 40 kV, 40 mA). 1 H-NMR spectrum. 1 H-NMR spectra were collected on a 300 MHz Bruker spectrometer. Chemical shifts were referenced to residual solvent peaks. Approximately 2 mg of MOF-808 was dissolved in 0.6 mL DMSO-d 6 Before diluting with 8 drops of D 2 SO 4 And digested it.
[0102] Diffuse reflectance infrared spectrum. The diffuse reflectance infrared spectrum has a resolution of 1 cm. ―1 The spectra were collected using a Thermo Scientific Nicolet 6700 FT-IR equipped with a liquid nitrogen cooled MCT detector.
[0103] SEM and X-ray spectroscopy. Scanning electron microscope (SEM) images and energy dispersive X-ray spectroscopy data were collected on a Phenom ProX desktop SEM.
[0104] Activation of MOFs. MOF samples were activated using a Micrometrics SmartVacPrep instrument equipped with a hybrid turbo vacuum pump.
[0105] BET surface area. BET surface area is between 0.0005 and 0.1 P / P, meeting all BET criteria0 The calculation is performed using the points on the isotherm between
[0106] Nitrogen adsorption-desorption isotherms. Nitrogen adsorption-desorption isotherms were measured at 77 K on a Micromeritics TriStar II Plus instrument.
[0107] ICP-MS. Inductively coupled plasma mass spectrometry (ICP-MS) data were recorded on an Agilent 7500 series. Standards were prepared at 0.05, 0.1, 0.2, 0.5 and 1 ppm I by serial dilution with 0.5% (v / v) ammonium hydroxide solution. - Concentrations were prepared.
[0108] X-ray total scattering. X-ray total scattering measurements were performed using beamline P02.1 of Petra III at the Deutsche Elektronen Synchrotron (DESY), Hamburg, Germany. Data were captured on a 2D VAREX XRD4343 CT detector (2880 × 2880 pixels, 150 × 150 μm each) mounted orthogonally to the beam path. 2 ) in fast acquisition mode. The sample was packed into a 1 mm diameter glass capillary and the sample-to-detector distance was 499.0 mm. The incident energy of the X-ray beam was 59.58 keV (λ = 0.20729 Å). 6 The detector position was calibrated using the program PDFgui: 14 Q damp =0.0170Å -1 is characterized by fitting the structure of the calibration standard to
[0109] Data reduction. Calibration of the detector geometry and image integration were performed using the azimuth integration software pyFAI. Raw data images were summed, corrected for polarization effects, and then masked and azimuthally integrated to generate 1D powder diffraction patterns. Further normalization and conversion to real-space PDF was performed using PDFgetX3 in xPDFsuite. The total scattering structure function S(Q) is calculated by multiplying the coherent scattering intensity I by the self-scattering removal by c (Q) is the starting point.
number
number
number
number
[0110] For differential PDF analysis, in order to minimize the presence of the termination effect in real-space signals, the Fourier transform (Q max =20.7Å -1 ) before the correction function M(Q) 19 was multiplied by F(Q). To evaluate the systematic error introduced by the differential PDF (dPDF) extraction method, the dPDF was extracted using four different subtraction methods. 1. Direct subtraction of the empty MOF from the intensity of the loaded MOF in reciprocal space. 2. Subtract in real space by optimizing the scale of the PDFs of the empty and loaded MOFs in the range of 1.5–6 Å. 3. Subtract in real space by fitting the empty MOF PDF to the loaded MOF PDF. The empty MOF PDF was modified by a spherical domain attenuation function, adding a damped sine wave to adjust for differences in atomic density. 4. Same as above: the blank MOF PDF was further modified by a magnification factor so that the signal could be scaled to best fit the loaded MOF PDF signal.
[0111] The systematic uncertainty in the experimental dPDF was then estimated as the standard deviation among the four different extraction methods. 3 A model dPDF was simulated from the cluster, considering the atom pairs between the I and O atoms of the motif (not bound to the cluster) with each other and with the remaining atoms. Diffpy - CMI Software 7 Debye function calculator, Q range =1.0~20.0Å -1 and B. iso =1.0Å 2 Used in.
[0112] Additional diffraction measurements. To verify the sample structure, additional measurements were performed on the sample using a STOE Stadi-P diffractometer with CuKα radiation (λ=1.540596 Å, scanned over the range 0.0-115.0°2θ with a Ge(111) Johann monochromator and a single Mythen detector over a period of approximately 3.7 hours). The sample was loaded into a 0.7 mm diameter borosilicate capillary tube and rotated during the measurements for optimal orientation sampling of the powdered crystallites.
[0113] Pawley and Rietveld refinements. Pawley and Rietveld refinements are supported by TOPAS v5 / v6. 22 In both cases, refinements were performed taking into account the Fd-3m symmetry of the cubic crystal form, together with the Gaussian and Lorentzian contributions to the broadening of the peak profile, and the Stephen model of distortion (three parameters). Further calibrations included a zero-offset calibration, the parameter of the sample length in the all-axis model for the asymmetry of the peaks, and the Lorentzian polarization factor for the given radiation and monochromator. Complex backgrounds were described using a combination of Chebyshev polynomials and a broad Gaussian peak, or using the phase of the second hkl with a fixed peak broadening set to 1 nm. Additional pseudoatoms with atomic displacement parameters fixed to larger values were added to account for the water content of the pores and the amount of bound water or IO. 3 is included to illustrate.
[0114] Regeneration. To test the reusability of MOF-808 in multiple adsorption cycles, 10 mg of MOF-808 was exposed to 10 mL of 1148 ppm potassium iodate solution (7 iodate anions per node) overnight. The MOF powder and iodate solution were then placed in the membrane filter of a glass microfiltration apparatus equipped with a vacuum pump. The iodate solution was drawn through the membrane, the filtrate was collected, and the MOFs on the membrane were washed with 3x10 mL of water. Then, 10 mL of 1%, 3%, 5%, or 10% HCl was drawn through the MOF sample over the course of 5 min by vacuum manipulation. An aliquot (100 μL) of the acidic filtrate was taken immediately after filtration and diluted 2000-fold by serial dilution with 0.5% ammonium hydroxide. To determine the amount of iodate removed from the MOFs by acid washing, the iodine concentration was measured by ICP-MS. After washing with acid, the MOF on the membrane was washed again with 3x10mL of water. The powder was then soaked overnight in a fresh solution of 1148ppm potassium iodate to begin the next adsorption cycle. Three adsorption-desorption cycles were performed.
[0115] To evaluate the porosity after recycling, five batches of 10 mg of MOF-808 were loaded with iodate and regenerated with 10% HCl as described above. After the third cycle, the MOF samples were bonded, washed three times with 20 mL water and three times with 20 mL acetone, and left soaked in acetone overnight before activation and BET measurements.
[0116] To evaluate the porosity of MOF-808 after adsorption, 50 mg of MOF-808 was exposed to 50 mL of potassium iodate solution at 1148 ppm (7 iodate anions per node) overnight. The iodate-loaded sample was washed three times with 20 mL of water and three times with 20 mL of acetone and soaked in acetone overnight before activation and BET measurements.
[0117] For the nitrogen adsorption-desorption isotherms presented in FIG. 9B, 234.0 mg, 20.1 mg, and 33.2 mg of MOF were used for the analysis of MOF-808, MOF-808+iodate, and HCl-regenerated MOF-808, respectively.
[0118] Various embodiments of the present invention have been described above. However, it should be understood that alternative embodiments are possible and the present invention is not limited to the specific embodiments described above. For example, the present invention is not necessarily limited to the treatment of liquids or liquid streams associated with nuclear power plants. Other industrial streams or liquids containing iodine species as described above can be removed using the methods and MOFs described herein. Similarly, the methods of regenerating MOFs described herein can also be used to regenerate MOFs used in other industrial processes.
Claims
1. 1. A method for removing iodine species from a liquid, comprising: contacting the MOF-808 with a liquid containing iodine species; The method comprises a step of adsorbing the iodine compound onto the MOF-808.
2. The iodine species is I - Or IO 3- The method of claim 1, wherein
3. The method of claim 1 , wherein the iodine species comprises an oxyanion of iodine.
4. The method of claim 3 , wherein the oxyanion of iodine comprises an iodate.
5. regenerating the MOF-808 after said adsorption to remove said iodine species from said MOF-808. The method of claim 1 further comprising:
6. The regeneration step comprises: contacting the MOF-808 with an acid cleaner The method of claim 5 , comprising:
7. The method of claim 6 , wherein the acid cleaner comprises HCl.
8. adsorbing additional iodine species after said regeneration. The method of claim 5 further comprising:
9. 1. A method for regenerating a sorbent used to remove iodine species from a liquid, comprising the steps of: contacting the MOF-808 containing the adsorbed iodine species with an acid cleaner. A method comprising:
10. The method of claim 9 , wherein the acid cleaner comprises HCl.
11. The iodine species is I - Or IO 3- The method according to claim 9, wherein
12. 10. The method of claim 9, wherein the iodine species comprises an oxyanion of iodine.
13. 13. The method of claim 12, wherein the oxyanion of iodine comprises an iodate.